The Role of Auditing in Corporate Governance in Australia and New Zealand: A Research Synthesis. Issue 4 (9th August 2017) - Hay, David; Stewart, Jenny; Botica Redmayne, Nives
Abstract: Corporate governance is of growing importance in Australia, New Zealand and all over the world. Corporate governance interacts with auditing and it is useful to understand how corporate governance and auditing affect companies. A related issue is whether better governance is a substitute for auditing or a complement. Previous studies of that issue have had mixed results. This review article provides a synthesis of Australian and New Zealand research about corporate governance and auditing that assesses what has been found and examines issues that can be explored using multiple studies. We conclude that despite extensive research, there is still considerable uncertainty about how corporate governance mechanisms are related to auditing and how auditing is associated with corporate governance. We conclude that recommendations for better governance (beyond a minimum level) are not yet supported by evidence. The results are intended to be helpful in providing advice about policy in Australia and New Zealand, and in determining directions for new research. Abstract : This synthesis assesses Australian and New Zealand research about corporate governance and auditing. We conclude that despite extensive research, there is still considerable uncertainty about how corporate governance mechanisms are related to auditing and how auditing is associated with corporate governance.